Cooking the Books: The Ethical Implication of Performance Management on Timely Services for Veterans. (4th March 2018) - Patrick, Barbara A.; Plagens, Gregory K.
Abstract : The integrity of the performance reform movement is vulnerable to manipulation because of strains on the principal–agent relationship, yet the quality of performance reforms has been understudied. This case study assesses performance reforms by examining the Veterans Health Administration's development and implementation of a measure of timely medical services for veterans. The analysis reveals that ambitious goals and underdeveloped training programs contributed to unethical actions and data manipulation. Investments in elements crucial to a successful principal–agent relationship and performance measures accounting for ethical behavior could result in more meaningful uses of performance reforms.